Influence of Retanning Agents on Physical Characteristics of Snow-White Glove Leather from Goat Skin - Yuliatmo, Ragil; Maryati, Tutik; Rahmawati, Atiqa; Adamu, Dahiru J M; Mizan, Al (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The quality of leather is subject to various elements, such as the specific raw material used, and the processing techniques implemented throughout the production process. Goatskin, renowned for its exceptional softness and durability, is frequently employed in the production of gloves owing to its desired attributes, notably its capacity to produce snow-white gloves. Retanning is an essential step in the leather manufacturing process as it significantly improves the characteristics of the leather. Through an investigation into the impacts of distinct retanning agents on goatskin leather gloves, this research endeavor seeks to offer significant knowledge regarding the most effective retanning procedures that can augment the tactile attributes of snow- white leather gloves. In this study, formaldehyde, alum, chromium, and chromium alum were employed as retanning agents. The retanned leathers were assessed by physical parameters, Principal Component Analysis (PCA), and Fourier Transform Infrared spectroscopy (FTIR), then compared to a commercially available snow-white leather glove. The physical characteristics of chrome alum retanned leather showed a high degree of softness (6.60±0.02 mm), good tear strength (1.530±117 N/cm), and tensile strength (1.500±100 N/cm 2 ). The principal component analysis (PCA) also supported that the properties of chrome alum retanned snow-white glove leather closely resemble commercial leather and the result from this study suggested that all factors notably impact the skin's physical quality, except for thickness. Additionally, the FTIR analysis reveals similar functional groups from the different retanned leathers indicated by comparable peaks and stretching patterns. Therefore, chrome-alum could be a well alternative retanning agent for the production of snow-white glove leather.